The role of Catholic schools in promoting human dignity - Kleindienst, Petra (British Journal of religious education, 2022)
The article addresses the role played by Catholic schools in promoting human dignity among young people. This is a study of Catholic/public high schools in Santa Clara County, California, the USA. It involves qualitative research conducted in public and Catholic private high schools. A comparison of the research results for these two school types shows the Catholic private high schools included in the research have a significant impact on both understanding of the concept of human dignity and promoting human dignity among the young students who attend these schools. In this regard, the research results reveal that legislation and thus administration play an important role in promoting human dignity through the education system. The legislative level is thus able to substantially accelerate/impede the efforts of the education system to adapt to not only social dynamics and changes but the prevalent tendencies of individuals, religion and society.